Promoting technological innovation in the Swedish cardiac imaging market: success factors for bayer to facilitate product adoption and market entry - Uerkuet, Koray (2023)
Technological innovation is an important growth driver in the pharmaceutical industry. This work project deals with how Bayer as a pharmaceutical company can promote the usage of Coronary Computed Tomography Angiography (CCTA) in Sweden and analyzes the success factors for a market entry of Bayer’s CCTA solution, which involves contrast media. Combining a review from interviews from the business project and a literature research consisting of academic studies, industry reports and regulatory documents, the work project suggests research support and funding on the advantages of CCTA and partnerships with producers of CCTA machines as the success factors for market entry.